Implementation and evaluation of r-safe race: a play-based road safety education programme among primary school children - Shahril, Roziana; Sidek, Suriati; Ab. Rashid, Ahmad Azad (Secholian Publication, 2026)
Road safety education (RSE) is a vital component of primary school curricula to instil safe road behaviours early. However, traditional classroom-based approaches such as Pendidikan Keselamatan Jalan Raya (PKJR) may lack engagement and developmental appropriateness. This study implemented and evaluated the R-Safe Race, a play-based RSE programme designed for Malaysian primary school children aged 10–12, following the ADDIE instructional design model. The programme was conducted as an outdoor exploration race featuring six thematic checkpoints addressing key road safety topics. A total of 164 students participated, and their perceptions of content clarity, relevance, interest, understanding, and learning gains were assessed through a structured questionnaire using a 5-point Likert scale. Findings showed strong engagement and positive perceptions overall, with particularly high ratings for checkpoints on car passengers and cyclist behaviour. Participants reported increased self-efficacy to adopt safer behaviours and found the facilitators effective. However, lower ratings on the transportation and vehicle safety checkpoints suggest areas for improvement. The results support play-based learning as an effective pedagogical approach to enhance engagement, understanding, and self-regulation in RSE. This study highlights the need to diversify RSE delivery methods to align with children’s developmental needs, suggesting that outdoor, guided play activities offer significant benefits over traditional approaches